2006
DOI: 10.1037/1064-1297.14.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine lowers brain stimulation reward (BSR) threshold in alcohol-preferring (P) and non-preferring (NP) rats: Regulation by D₁ and D₂ receptors in the nucleus accumbens.

Abstract: Differences in the mesolimbic dopamine (DA) pathway that regulates alcohol preference may also increase sensitivity to the reinforcing effects of other drugs of abuse. In the present study, the curve-shift (rate-frequency) paradigm was used to quantify the interaction of amphetamine with the rewarding effects of lateral hypothalamic brain stimulation reward (BSR) in alcohol-preferring (P) and -nonpreferring (NP) rats. The role of D-sub-1 and D-sub-2 DA receptors of the nucleus accumbens (NAcc) in mediating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…Also, while not statistically significant, the 5.0 mg dose of SCH 23390 did mildly reverse the reduction in EF 50 seen with amphetamine alone. Recent work from our laboratory shows similar effect of SCH 23390 on amphetamine potentiated BSR reward in the MFB (Eiler et al, 2006). These data are consistent with a recent study single-unit recording study by Cheer et al (2005) that demonstrates that SCH 23390 attenuates neural activity in the NAC during intracranial self-stimulation in the MFB.…”
Section: Discussionsupporting
confidence: 90%
“…Also, while not statistically significant, the 5.0 mg dose of SCH 23390 did mildly reverse the reduction in EF 50 seen with amphetamine alone. Recent work from our laboratory shows similar effect of SCH 23390 on amphetamine potentiated BSR reward in the MFB (Eiler et al, 2006). These data are consistent with a recent study single-unit recording study by Cheer et al (2005) that demonstrates that SCH 23390 attenuates neural activity in the NAC during intracranial self-stimulation in the MFB.…”
Section: Discussionsupporting
confidence: 90%
“…Fourth, our observation that D1 and D2 agonists have very similar effects that are the opposite of the effects of D1 and D2 antagonists has important implications for conclusions about the specificity of the drugs' effects. In most previous studies, microinjected D1 and D2 antagonists had very similar behavioral (Hiroi and White, 1991 ; Ozer et al, 1997 ; Koch et al, 2000 ; Yun et al, 2004b ; Eiler et al, 2006 ; Pezze et al, 2007 ; Lex and Hauber, 2008 ; Liao, 2008 ; Nicola, 2010 ; Shin et al, 2010 ; Haghparast et al, 2012 ; Steinberg et al, 2014 ) and electrophysiological (du Hoffmann and Nicola, 2014 ) effects. Because the concentration of injected antagonists required to observe effects is much higher than the binding constants of these drugs for their target receptors, the similarity of D1 and D2 antagonist effects calls into question their specificity: it is possible that the drugs either bind to the same dopamine receptor, or to a third receptor class that is not a dopamine receptor at all.…”
Section: Discussionmentioning
confidence: 78%
“…All of the C57 mice learned to turn the wheel and reached criteria within the first session whereas the successful DBA mice on average took longer to reach the same criteria. Previous studies in inbred or selectively bred mouse or rat strains have generally either not found or not described differences in the rate of learning an operant for brain stimulation reward (Cazala and Cardo 1977; Cazala et al 1974; Cazala and Guenet 1979; Eiler et al 2007; Eiler et al 2006; Eiler et al 2005; Garrigues and Cazala 1983; Ranaldi et al 2001; Woods et al 2003; Zacharko et al 1990). The delay seen in the DBA mice is not the result of a general learning deficit since DBA mice learn to lever press (water training prior to i.v.…”
Section: Discussionmentioning
confidence: 99%